Study of the inventory of a service provider (Research, Society and Development, 2021)
This paper aims to present and discuss characteristics and features of inventory management, showing it’s importance in the internal processes of the company and demonstrating how the management and reliability of its data can generate impacts. A study was conducted in a company that provides maintenance services for electric motors, which acts as a supplier of goods and services to one of the main national steel supply companies, among other companies in the mining, cement, steel and food industries. This study is classified as an action-research that begins with data collection, in addition to qualitative analysis for which brainstorming, quality tools, and informal interviews were used. Through these tools, results were obtained that point to the waste of financial resources, it was proven that only the implementation of an ERP system is not enough to maintain a high accuracy of the stock, being necessary to apply continuous improvement in order to make the most of the company's resources.